The Evolution of Islamic Preaching by the Existence of Smartphones - Setiawan, Arief Tri; Rahmayuni, Dewi; Hermansah, Tantan; Gazi, Gazi; Muhtadi, Muhtadi; Rizky, Kiky (Jurnal Pekommas, 2022)
This study aims to get an overview of the development of Islamic Preaching through smartphones in the digital era. This study uses a qualitative method with a phenomenology design. This study examined the phenomenon of the booming of Preaching content on social media since Preaching through social media is currently in demand, as indicated by the emergence of a large number of the preacher, especially in Indonesia. The experience and motive of such phenomenon became the basis of this study’s analysis using phenomenological methods and Alfred Schutz’s theory. The results demonstrated a change in the Preaching of the preacher. The spirit of delivering Preaching (through writings) is based on two types of motives. First, individuals are eager (to) receive a blessing from Allah and be ‘ghirah.’ Second, the convenience and facilities available in smartphone technology have triggered the development of social media platforms that eventually support the delivery of Preaching.